Science, Technology and Innovation: the challenges of strengthening the national innovation system of Angola - Eurico Josue Ngunga (2015)
Starting from the idea that a societys whole system is the product of its norms, values, practices, and history (KUADA, 2003), I believe that the process of innovation will depend on these elements for the success of sustainable development. As pointed out by the United Nations, sustainable development does not only concern the interdependent links between environment and development, but also includes a concern for issues such as human rights, population, housing, food security and gender that are important parts of sustainable human development (www.unesco.org, accessed in 11/11/2014). These elements underscore a range of knowledge and skills that will serve as a lever for the development of a society, through its scientific and technological actions. The objective of this study was to analyze and discuss the specific challenges of strengthening a National System of Science, Technology and Innovation (NIS)1 in Angola, in order to put the country into the pathway of development, and to reduce existing asymmetries between its people. Determinants such as culture, history, the struggle for independence, civil war, educational processes and the gaps among peripheral countries and the Organization of Economic Cooperation and Development (OECD) countries were crucial to answer the questions proposed for this work. For this purpose,I investigated the Angolans who participated in the drafting of the National Policy on Science, Technology, and Innovation of Angola. In this vein, following several readings from various sources related to STIP, an attempt was made to perceive and analyze the strategies around the systematization of these policies for socio-economic development, taking into account the new socio-political scenario and Angolas aspirations for economic development in the period following the civil war that lasted 27 years. Moreover, I augmented with a survey on three institutions located across the country in order to strengthening the approach around the difficulties they have been facing in the post civil war. One of the big issues is the struggle to rebuild infrastructure destroyed during that hard moment. Several research techniques were combined: in-depth interviews with senior stakeholders from the Ministry of Science and Technology and Rectors, and an analysis of secondary sources. I also used a checklist to survey and verify statistical data. The overall findings are that Angola still does not have in its structures, capabilities to effectively monitor, and control the challenges perpetrated by the global economic market. This landscape puts the country almost always in a lower position in the field of R&D, and knowledge transfer, including trade. Thus, concluding, Angolas national system of innovation is currently incipient and its level of unpreparedness and instability requires improvements in its institutional structures and training in order to effect socio-economic development. Keywords: innovation, innovation system, economic development, civil war, sustainable development, Angola.